Observation of excess J/[psi] yield at very low transverse momenta in Au+Au collisions at √sNN=200 GeV and U+U collisions at √sNN=193 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review letters, 2019)
We report on the first measurements of J/ψ production at very low transverse momentum (pT<0.2 GeV/c) in hadronic Au+Au collisions at √sNN=200 GeV and U+U collisions at √sNN=193 GeV. Remarkably, the inferred nuclear modification factor of J/ψ at midrapidity in Au+Au (U+U) collisions reaches about 24 (52) for pT<0.05 GeV/c in the 60%-80% collision centrality class. This noteworthy enhancement cannot be explained by hadronic production accompanied by cold and hot medium effects. In addition, the dN/dt distribution of J/ψ for the very low pT range is presented for the first time. The distribution is consistent with that expected from the Au nucleus and shows a hint of interference. Comparison of the measurements to theoretical calculations of coherent production shows that the excess yield can be described reasonably well and reveals a partial disruption of coherent production in semicentral collisions, perhaps due to the violent hadronic interactions. Incorporating theoretical calculations, the results strongly suggest that the dramatic enhancement of J/ψ yield observed at extremely low pT originates from coherent photon-nucleus interactions. In particular, coherently produced J/ψ’s in violent hadronic collisions may provide a novel probe of the quark-gluon plasma.